Welfare Activities by New Religious Actors Islamic Organisations in Italy and Switzerland - Banfi, Elisa (Palgrave Politics of Identity and Citizenship Series, 2018)
This book offers a comparative examination of Islamic welfare activities across urban areas in both Switzerland and Italy, in order to address general issues relating to the welfare engagement of Islamic organisations in Europe. Welfare Activities by New Religious Actors describes how Islamic organisations have been coordinated and structured in Geneva, Milan, Rome, and Zurich; four cities not yet analysed in the literature on Islamic welfare. It also explores the institutional opportunities and constraints are able to influence forms of social religious activities at the local and international level by bringing together two research fields that seldom speak to each other: social network analysis and political opportunity theory. This book will appeal to scholars of Sociology, Anthropology and Religious Studies dealing with the social and political inclusion of Muslims in Europe and the social activities of Islamic organisations in Western countries.